Accuracy of C-reactive protein, procalcitonin, serum amyloid A and neopterin for low-dose CT-scan confirmed pneumonia in elderly patients: A prospective cohort study. - Virginie Prendki; Astrid Malézieux-Picard; Leire Azurmendi; Jean-Charles Sanchez; Nicolas Vuilleumier; Sebastian Carballo; Xavier Roux; Jean-Luc Reny; Dina Zekry; Jérôme Stirnemann; Nicolas Garin; PneumOldCT study group (PLoS ONE, 2020)
Objective The diagnosis of pneumonia based on semiology and chest X-rays is frequently inaccurate, particularly in elderly patients. Older (C-reactive protein (CRP); procalcitonin (PCT)) or newer (Serum amyloid A (SAA); neopterin (NP)) biomarkers may increase the accuracy of pneumonia diagnosis, but data are scarce and conflicting. We assessed the accuracy of CRP, PCT, SAA, NP and the ratios CRP/NP and SAA/NP in a prospective observational cohort of elderly patients with suspected pneumonia. Methods We included consecutive patients more than 65 years old, with at least one respiratory symptom and one symptom or laboratory finding suggestive of infection, and a working diagnosis of pneumonia. Low-dose CT scan and comprehensive microbiological testing were done in all patients. The index tests, CRP, PCT, SAA and NP, were obtained within 24 hours. The reference diagnosis was assessed a posteriori by a panel of experts considering all available data, including patients' outcome. We used area under the curve (AUROC) and Youden index to assess the accuracy and obtain optimal cut-off of the index tests. Results 200 patients (median age 84 years) were included; 133 (67%) had pneumonia. AUROCs for the diagnosis of pneumonia was 0.64 (95% CI: 0.56-0.72) for CRP; 0.59 (95% CI: 0.51-0.68) for PCT; 0.60 (95% CI: 0.52-0.69) for SAA; 0.41 (95% CI: 0.32-0.49) for NP; 0.63 (95% CI: 0.55-0.71) for CRP/NP; and 0.61 (95% CI: 0.53-0.70) for SAA/NP. No cut-off resulted in satisfactory sensitivity or specificity. Conclusions Accuracy of traditional (CRP, PCT) and newly proposed biomarkers (SAA, NP) and ratios of CRP/NP and SAA/NP was too low to help diagnosing pneumonia in the elderly. CRP had the highest AUROC. Clinical trial registration NCT02467092.